Low density Plasmodium infections and G6PD deficiency among malaria suspected febrile individuals in Ethiopia - Abagero, Beka R.; Kepple, Daniel; Pestana, Kareen; Witherspoon, Logan; Biruksew, Abdissa; Adanew, Abinet; Baharu, Fetiya; Hansel, Shantoy; Lopez, Karen; Janies, Daniel A.; Lo, Eugenia; Yewhalaw, Delenasaw (Frontiers in Tropical Diseases, 2022)
The identification and management of low parasitemia infections have become increasingly challenging for malaria control and elimination. Submicroscopic Plasmodium infections and G6PD deficiency among febrile patients require more sensitive diagnostic methods to improve detection and careful treatment regime of these infections. In Ethiopia, information on the low density submicroscopic malarial infections and frequency of G6PD deficiency (G6PDd) is scarce. In this study, 297 malaria suspected febrile patient samples were collected from health facilities of Bonga town in southwestern Ethiopia. The positivity rates of Plasmodium infection were determined by microscopy and quantitative PCR. G6PD activity level was determined by careSTART™ G6PD biosensor and the frequency of three common variants: G6PD*A (A376G), G6PD*A− (G202A) and Mediterranean (C563T) were investigated. G6PD gene sequencing was performed to detect mutations in exons 2–11 for both G6PD normal and deficient samples based on the phenotypic assay. More than twice Plasmodium infected samples was detected by qPCR (52/297; 17.4%) than microscopy (21/297; 7.0%). About 31 (10%) of the infections were submicroscopic. Bednet usage and age had a significant association with Plasmodium infection. Of the 271 participants who were tested for G6PD phenotype, 19 (7.0%) had low G6PD level. No mutations were observed in A376G, G202A, and C563T in the G6PDd samples, but three novel non-synonymous mutations in exon 2 including a C to T transition at position ChrX:6504 (Arg to Thr), G to T at ChrX:6369 (Ser to IIe), and G to C at ChrX:6664 (Gln to His) were detected. A high number of submicroscopic Plasmodium infections observed in this study pose a challenge for accurate and timely diagnosis, which could hinder malaria control efforts. G6PD deficiency in malaria patients pose danger when treating patients with primaquine. The three novel mutations detected in exon 2 of the G6PD gene merit further investigation on the hemolytic risk when exposed to oxidative antimalarials, their prevalence, and clinical significance.